Man-Made Major Hazards Like Earthquake or Explosion; Case Study, Turkish Mine Explosion (13 May 2014). - Jamileh Vasheghani Farahani (Tehran University of Medical Sciences, 2014)
In all over the world, mining is considered as a high-risk activity that is pregnant with serious disasters not only for miners, engineers, and other people into it, but also for people who live near the mines. In this article, our main purpose is to examine some major mine disasters and safety in mines and the case study is a coal mine in Turkey. Safety in mines is one of the most important issues that need attention. Therefore, it is suggested that existing deficiencies in mines should be removed by continuous monitoring in all devices, equipments, control of Methane and safe separation of coal from a mine. Moreover, we recommend that early warning systems should be installed to alert some explosions, fires and other dangerous events to the fire departments, hospitals, Red Crescent and other major reliefs. Experiences from previous events in mines can help managers and miners. With some plans and projects related to disasters in mines and solution for them, some diseases such as black lung disease or other problems in mines such as carbon monoxide poisoning can forestall a danger. Before Mine owners begin their activity, they must research about the environmental and social effects of their activities. Therefore, they should identify some important hazards and determine some essential tasks to remove them or control risks via collaboration with other scientists.